Innovative Exploration of Township Government in constructing a New System of Rural governance (Based on the Survey Report of the Squatting Research in Hengli Town, Dongguan city, Guangdong Province, China) - Qing Zhang (Управленческое консультирование, 2020)
Township governance is the foundation of national governance, related to the vital interests of ordinary people, affecting the stability and development of the country. At present, China’s economic growth are entering adjustment after transformation, the development and changes of the economic foundation needs a new concept of social governance, grassroots governance must focus on the new era of new requirements, from a strategic height to grasp the law of development of the township governance, governance from the Angle of practice innovation, promote social governance system construction needs to insist on the guidance, this article through to the horizontal drain in the town of Dongguan city, Guangdong province in grass-roots community diversity co-govermnet everybody is responsible for building, everyone is responsible for all the analysis of the community of social governance of exploration and practice, put forward to further improve township government countermeasures for establishing a new system of rural governance. In Hengli Town, positive measures are explored to improve the township level administrative management system and promote collaborative innovation of rural social governance in township governance capacity, providing reference for building a new system of rural governance and exploring the township level administrative management system.